Extended least squares support vector machines for ordinal regression. Issue 6 (August 2016) - Zhang, Na
Abstract We extend LS-SVM to ordinal regression, which has wide applications in many domains such as social science and information retrieval where human-generated data play an important role. Most current methods based on SVM for ordinal regression suffer from the problem of ignoring the distribution information reflected by the samples clustered around the centers of each class. This problem would degrade the performance of SVM-based methods since the classifiers only depend on the scattered samples on the border which induce large margin. Our method takes the samples clustered around class centers into account and has a competitive computational complexity. Moreover, our method would easily produce the optimal cut-points according to the prior class probabilities and hence may obtain more reasonable results when the prior class probabilities are not the same. Experiments on simulated datasets and benchmark datasets, especially on the real ordinal datasets, demonstrate the effectiveness of our method.